Are CD44⁺/CD24⁻ cells the assumed cancer stem cells in breast cancer? - Ryspayeva, D.E.; Smolanka, I.I.; Dudnichenko, A.S.; Lyashenko, A.A.; Grinevich, Yu.A.; Gurianov, V.G.; Koshubarova, M.V.; Seleznev, A.A. (Experimental Oncology, 2017)
Identification and characterization of the population of cancer stem cells (CSC) depends on several cellular markers, which combination is specific for the phenotype of CSC in the corresponding tumor. Several markers of CSC have already been identified in breast cancer (BC), but there are no universal indicators that could specifically identify the CSC in BC. Aims: To determine the validation of the CSC model for cell surface markers such as CD44 and CD24 and their clinical significance. Materials and Methods: Primary tumor samples of 45 patients with invasive BC without chemotherapy prior to surgery exposure were examined in paraffin blocks. CD44 and CD24 antigens expression was evaluated by the percentage of positive cells using different chromogens and the MultiVision detection system by immunohistochemical method. In this research the evaluation was determined by the following criteria: (-), negative — expression in < 10% of tumor cells; (+), positive — expression in ≥10% of cells. The same scoring system was applied for the expression of CD44⁺/CD24⁻. Results: 62.2% of investigated patients are patients older than 50 years and most of them with stage II of disease (71.0%) and luminal tumor subtypes (68.9%). We analysed the expression of CD44, CD24 and CD44⁺/CD24⁻ for different patients with dividing them into two groups. The group A consists of patients with unfavorable prognosis (relapses and metastases have occurred in the first three years after diagnosis), and the group B — with a favourable prognosis (the development of metastases after three years). Median disease-free survival in the group A is 19 months, in the group B — 46 months. The difference between the overall survival (OS) curves in the groups A and B is statistically significant (p < 0.001), the risk of death was higher in the group A (hazard ratio (HR) 5.9; confidence interval (CI) 2.3–15.2). The content of CD44 cells did not differ statistically between groups A and B (p = 0.18), but there was a tendency for increasing in OS with the existence of CD44+ cells (p = 0.056). The distribution of the expression of CD24 marker did not differ between the groups (p = 0.36) as well as the OS curves (p = 0.59). Analysis of the expression of CD44+/CD24⁻ which were considered as possible CSC, revealed a paradoxical increase (p = 0.03) of the frequency in patients of the group B (40.9%) compared to the group A (8.7%). Nevertheless, the comparison of the clinical outcomes did not reveal a statistically significant difference in the survival curves in the groups with existence and absence of CD44⁺/CD24⁻ expression (p = 0.08). The analysis showed the increasing of the risk of worse clinical outcomes in the cases of expression absence of CD44⁺/CD24⁻ (HR 2.8; CI 1.1–6.8). Conclusions: As a result of our research, the analysis of the quantity of assumed stem cells of the BC, which were identified by immunohistochemistry as CD44 and CD24 cells, failed to detect a statistically significant relation between groups of patients with different prognosis, and the identification of their expression is not enough for the characteristics of CSC. The obtained data demonstrating the worst clinical outcome in the cases of absence of CD44⁺/CD24⁻ expression apparently require further investigations and the validation of the immunohistochemical method with the determination of the cut-off line in defining of CD44 and CD24 status.